Reversible 2D/3D Coatings from Zipper‐Assembly of Block Copolymer Micelles. (10th June 2013) - Tyagi, Prashant; Raschip, Irina Elena; Deratani, André; Quemener, Damien
<x xml:space="preserve">Abstract</x> A zipper‐assembly of micelles into 2D/3D coatings is reported. Block copolymer micelles that incorporate a poly(n‐octadecyl methacrylate) block are zipped and unzipped on demand onto a PMMA surface. The mechanism implies an interdigitation of molecular brushes enabling 15 nm micelles to be assembled into monolayers or multilayers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>